2012
DOI: 10.1042/cs20110557
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin T levels and exercise stress testing in patients with suspected coronary artery disease: the Akershus Cardiac Examination (ACE) 1 study

Abstract: Whether reversible ischaemia in patients referred for exercise stress testing and MPI (myocardial perfusion imaging) is associated with changes in circulating cTn (cardiac troponin) levels is controversial. We measured cTnT with a sensitive assay before, immediately after peak exercise and 1.5 and 4.5 h after exercise stress testing in 198 patients referred for MPI. In total, 19 patients were classified as having reversible myocardial ischaemia. cTnT levels were significantly higher in patients with reversible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 13 publications
5
36
0
5
Order By: Relevance
“…This hypothesis also has some support in the literature. In a previous publication from the ACE 1 study, we found no association between reversible myocardial ischemia and the release of hs-cTnT during exercise stress testing (19 ). Although the modest number of patients with reversible ischemia in our study may increase the likelihood of a type II error, the lack of increment in hs-cTnT concentrations after exercise stress testing is in accordance with earlier results by Kurz et al (18 ).…”
Section: Reversible Ischemia (N ‫؍‬ 19)supporting
confidence: 81%
See 2 more Smart Citations
“…This hypothesis also has some support in the literature. In a previous publication from the ACE 1 study, we found no association between reversible myocardial ischemia and the release of hs-cTnT during exercise stress testing (19 ). Although the modest number of patients with reversible ischemia in our study may increase the likelihood of a type II error, the lack of increment in hs-cTnT concentrations after exercise stress testing is in accordance with earlier results by Kurz et al (18 ).…”
Section: Reversible Ischemia (N ‫؍‬ 19)supporting
confidence: 81%
“…The study protocol of the ACE 1 study has been reported (19,21 ). We included consecutive patients according to a stratified protocol with 50 patients included from the low-risk stratum (Ͻ33% probability of stable CAD), 100 patients from the intermediaterisk stratum (33%-67%), and 50 patients from the high-risk stratum (Ͼ67%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Повышение hs-cTnТ при дозированных нагрузоч-ных тестах у больных СтСт наблюдали также в иссле-довании АСЕ (Akershus Cardiac Examination Study) [21]. Исследования проведены у 198 пациентов, среди которых были здоровые лица и больные со СтСт.…”
Section: современные высокочувствительные методы определения тропонинunclassified
“…В результате этого сердечная мышца подвержена большему риску на-растания ишемии. После интубации существует риск об-острения ХОБЛ, что приводит к повышению ферментов, являющихся диагностическими критериями ОИМ [11]. Поэтому минимальные изменения на кардиограмме и по-следующие тесты на тропонин Т могут являться критери-ями выставления диагноза ИМ у больных с умеренными проявлениями ишемии.…”
Section: результаты и обсуждениеunclassified